Market Frictions, Interbank Linkages and Excessive Interconnections - Deb, Pragyan (IMF Working Papers; Working Paper ;, 2016)
This paper studies banks' decision to form financial interconnections using a model of financial contagion that explicitly takes into account the crisis state of the world. This allows us to model the network formation decision as optimising behaviour of competitive banks, where they balance the benefits of forming interbank linkages against the cost of contagion. We use this framework to study various market frictions that can result in excessive interconnectedness that was seen during the crisis. In this paper, we focus on two channels that arise from regulatory intervention-deposit insurance and the too big to fail problem.